Survival Rate of Implants and Mechanical Complications for 64 Implant-Supported Complete-Arch Prostheses in Maxillary Edentulous Patients with a Follow-up of up to 12 Years: A Cross-Sectional Analytical Study - Younes, Ibrahim Abazar; Able, Francine Badin; De Moraes, Kely Cristina; Sartori, Ivete Aparecida de Mattias (The International journal of oral and maxillofacial implants, 2024)
To identify the technical complications associated with maxillary complete-arch implant-supported fixed prostheses (ISFPs) and to evaluate the survival rates of both dental implants and prostheses. In addition, we sought to analyze the impact that the presence of cantilevers, the type of prosthetic abutment, and the number of implants have on the occurrence of complications. Data were obtained from standardized clinical assessments carried out in a single appointment by two calibrated professionals (F.B.A. and I.A.Y.) using information from dental records. The sample consisted of 64 patients rehabilitated with ISFPs classified as hybrid prostheses (metal-resin). The survival rate for implants was 98.6% after 1 to 12 years (5.2 years ± 36.6 months) and was 100% for the prostheses after a follow-up of 12 to 144 months (mean: 48.1 ± 33.94 months). The most frequent complications were occlusal wear (82.8% of patients) as well as loosening of prosthetic screws (16.6%) and abutments (8.1%). The screw loosening frequency was significantly greater in 30-degree abutments compared with straight abutments (P = .008), but no significant difference was found between 17-degree and 30-degree abutments. Prostheses with a higher occurrence of screw loosening had a greater average cantilever length/anteroposterior spread (CL/AP) ratio (0.9 ± 0.5). In addition, abutments placed on distal implants were more likely to loosen (P < .001). The absence of mutually protected occlusion did not significantly influence the loosening of prosthetic screws and abutments. Implant-supported fixed maxillary complete-arch rehabilitations have high survival rates but are subject to technical complications.